ACCOMPLISHING COHERENCE IN TALK SHOWS: A COMPARISON BETWEEN ENGLISH AND INDONESIAN - Shanti, Yana (Universitas Pendidikan Indonesia, 2014)
Abstract: This paper tried to show how conversational coherence is achieved within talk shows, what strategies used by both host and interviewee to achieve coherence collaboratively. It was shown that in both English and Indonesian talk shows, conversational activity of asking questions can be employed to measure a coherence of a stretch of conversation. Question-answer adjacency pairs can provide the framework through which coherence is achieved, and they have two possibilities to be agreed or disagreed with. This is clear from the English talk show instead of the Indonesian one. The way speakers taking turn and the occurrence of overlap within the sequence of conversation can also determine mutual understanding among the participants. However, the Indonesian talk show offers a longer answer pair compared with the English one. Both talk shows, in fact, share the similar indicators and use similar strategies in order to achieve coherence across the talk show sessions. Speaker’s hesitation is found more in the Indonesian talk show instead of the English one. Another marker of coherence, overlap onset, also occurs a lot in both talk shows. The way speakers (host and interviewee) maintain the topic throughout the talk supports the notion that mutual understanding is successfully achieved. Meanwhile, culture is considered not too influential in determining different ways of maintaining the flow of the talk. Both talk shows use similar patterns with no significant difference in terms of culture. They differ only in the level of conversational devices used which is related to language use instead of cultural background. Keywords: coherence, adjacency pairs, turn-taking, talk shows Abstrak: Studi ini mencoba menunjukkan bagaimana koherensi percakapan dicapai dalam talk show, strategi apa yang digunakan oleh pembawa acara serta tamu yang diwawancarai untuk mencapai koherensi secara kolaboratif. Hal ini menunjukkan bahwa dalam talk show berbahasa Inggris maupun Indonesia, cara mengajukan pertanyaan dapat digunakan untuk mengukur koherensi dalam percakapan. Pasangan bersesuaian (adjacency pairs) dapat memberikan kerangka di mana koherensi dicapai, hal ini lebih jelas terlihat dalam talk show berbahasa Inggris. Cara mengambil giliran tutur dan terjadinya tumpang tindih dalam urutan percakapan juga dapat menentukan pemahaman di antara penutur. Dalam talk show berbahasa Indonesia, pemberian jawaban yang mengandung keragu-raguan lebih banyak ditemukan. Kedua talk show menunjukkan indikator yang sama dan menggunakan strategi yang sama untuk mencapai koherensi dalam sesi tanya jawab. Tumpang tindih kalimat (overlap onset), juga banyak ditemukan dalam kedua talk show. Cara pembawa acara dan tamu yang diwawancarai untuk mempertahankan topik pembicaraan menunjukkan bahwa saling pengertian berhasil dicapai. Sementara itu, kebudayaan dianggap tidak terlalu berpengaruh dalam menentukan perbedaancara dalam mempertahankan alur pembicaraan. Pada kedua talk show tidak ditemukan perbedaan yang signifikan dalam hal budaya. Mereka hanya berbeda dalam tingkat perangkat percakapan yang digunakan yang berkaitan dengan penggunaan bahasa bukan latar belakang budaya. Kata kunci: koherensi, pasangan bersesuaian, giliran tutur, talk shows